The Effect of Microwave Heating on the Extraction Yield and Elemental Composition of Black and White Pepper (piper nigrum) Extracts - Olalere, Olusegun Abayomi; Nour, A. H.; R. M., Yunus; Alara, Oluwaseun Ruth (Universiti Malaysia Pahang, 2017)
Black and white peppers are functional crops, used in food industries as spice and in traditional medicine, for the treatment of many degenerative diseases. This study investigated the influence of microwave heating on the extraction yield, energy absorption and dietary elemental composition of oleoresin extracts from black and white pepper. Under the largest donating rule, the maximum extract yield obtained was 48.22 mg/g from black pepper and 79.02 mg/g from white pepper microwave. The study therefore elucidated the energy absorption capacities in microwave heating and its resultant effects on extraction yield. This clearly showed the potentials of microwave technology in obtaining high quality extracts with properly controlled parameters.